Anxiolytic effect of estradiol in the median raphe nucleus mediated by 5-HT1A receptors - Andrade, TGCS; Nakamuta, J. S.; Avanzi, V; Graeff, F. G. (Elsevier B.V., 2005)
Estrogen deficiency has been associated with stress, anxiety and depression. Estrogen receptors have been identified in the median raphe nucleus (MRN). This structure is the main source of serotonergic projections to the hippocampus, a forebrain area implicated in the regulation of defensive responses and in the resistance to chronic stress. There is evidence showing that estrogen modulates 5-HT1A receptor functions. In the MRN, somatodendritic 5-HT1A receptors control the activity of serotonergic neurones by negative feedback. The present study evaluated the effect of intra-MRN injection of estradiol benzoate (EB) (600 or 1200 ng/0.2 mu l) on the performance of ovariectomised rats submitted to the elevated plus-maze test of anxiety and to the open-field test. Additionally, the same effect was evaluated with a previous intra-MRN injection of WAY 100635 (100 ng/0.2 mu l), an antagonist of 5-HT1A receptors. The results showed that both doses of EB increased the percentage of entries and the percentage of time spent into the open arms, suggestive of an anxiolytic effect. The highest dose of the drug also increased the number of entries into the enclosed arm and locomotion in the open field, indicating a stimulatory motor effect. WAY 100635 antagonised the effect of estradiol in the elevated plus-maze and in the open-field. The results show that estrogen receptors of the MRN are implicated in the regulation of anxiety-related behaviour. The results also support claims that the effect of estrogen involves a change in 5-HT1A receptor function. (C) 2005 Elsevier B.V. All rights reserved.
Keywords: median raphe nucleus; estradiol; anxiety; elevated plus-maze; open-field; serotonin